(untitled) (Bulletin of Innovative Research, 2026)
It studies the scientific and practical foundations of the technology of harvesting, primary processing and storage of tobacco leaves. Timely and correct harvesting of tobacco leaves is of great importance in maintaining the quality of the product and ensuring its technological properties. The influence of drying, fermentation and storage conditions of tobacco leaves, including temperature, humidity and air exchange, on the quality of the product was also analyzed. Based on scientific data, recommendations were developed to maintain quality indicators of tobacco leaves during storage, reduce losses and prepare recyclable raw materials. It is of great importance in increasing the efficiency of tobacco product production and forming a high-quality raw material base.